Postcontrast T1 Mapping for Differential Diagnosis of Recurrence and Radionecrosis after Gamma Knife Radiosurgery for Brain Metastasis - Wang, B.; Zhang, Y.; Zhao, B.; Zhao, P.; Ge, M.; Gao, M.; Ding, F.; Xu, S.; Liu, Y. (American Journal of Neuroradiology, 2018)
BACKGROUND AND PURPOSE: The differential diagnosis of radionecrosis and tumor recurrence in brain metastases is challenging. We investigated the diagnostic efficiency of postcontrast T1 mapping in solving this problem.MATERIALS AND METHODS: Between March 2016 and June 2017, fifty-six patients with brain metastases who underwent contrast-enhanced cerebral T1 mapping were recruited for this prospective study. The findings revealed new enhancement after gamma knife radiosurgery. The subjects were assigned to radionecrosis and recurrence groups based on follow-up (median, 11.5 months) and histopathologic results. T1 values of lesions 5 (T15min) and 60 (T160min) minutes after administration of contrast agent and their difference (T1differ) were compared between the 2 groups with the 2-tailed Mann-Whitney U test. Receiver operating characteristic curves were used to determine the optimum cutoff values for differential diagnosis.RESULTS: There were significant differences between the 2 groups in T15min, T160min, and T1differ values (P = .012, P = .004, and P < .001, respectively). Relative to T15min and T160min, T1differ exhibited greater sensitivity and specificity (P < .001, respectively) in identifying radionecrosis. The optimum T1differ value for differential diagnosis was 71.1 ms (area under the curve = 0.97; 95% CI, 0.93–1.00), with sensitivity and specificity of 81.5% and 96.5%, respectively.CONCLUSIONS: Postcontrast T1 mapping is optimal for the differential diagnosis of radionecrosis and tumor recurrence. Among T1 parameters, T1differ is the most powerful parameter for differential diagnosis. Advantages in terms of quantitative analysis and high resolution portend the wide use of postcontrast T1 mapping in the future.AUCarea under the curveBMbrain metastasesGKRgamma knife radiosurgeryrCBVrelative cerebral blood volumeT15minT1 values at 5 minutes after contrast administrationT160minT1 values at 60 minutes after contrast administrationT1differthe difference between T160min − T15min